Glyceride‐Mimetic Prodrugs Incorporating Self‐Immolative Spacers Promote Lymphatic Transport, Avoid First‐Pass Metabolism, and Enhance Oral Bioavailability. (2nd August 2016) - Hu, Luojuan; Quach, Tim; Han, Sifei; Lim, Shea F.; Yadav, Preeti; Senyschyn, Danielle; Trevaskis, Natalie L.; Simpson, Jamie S.; Porter, Christopher J. H.
Abstract: First‐pass hepatic metabolism can significantly limit oral drug bioavailability. Drug transport from the intestine through the lymphatic system, rather than the portal vein, circumvents first‐pass metabolism. However, the majority of drugs do not have the requisite physicochemical properties to facilitate lymphatic access. Herein, we describe a prodrug strategy that promotes selective transport through the intestinal lymph vessels and subsequent release of drug in the systemic circulation, thereby enhancing oral bioavailability. Using testosterone (TST) as a model high first‐pass drug, glyceride‐mimetic prodrugs incorporating self‐immolative (SI) spacers, resulted in remarkable increases (up to 90‐fold) in TST plasma exposure when compared to the current commercial product testosterone undecanoate (TU). This approach opens new opportunities for the effective development of drugs where oral delivery is limited by first‐pass metabolism and provides a new avenue to enhance drug targeting to intestinal lymphoid tissue.